KEINFORMATIFAN HARGA SAHAM DALAM KAITANNYA DENGAN EFISIENSI INVESTASI - Bahtiar Usman (Universitas Trisakti, 2006)
According to the Efficient Market Hypothesis, greater firm specific stock price variation reflects higher intensity firm specific information capitalization in stock price. In this study we propose that higher firm specific price variation maybe an indicator of greater functional-form market efficiency. We regress PER (Price to Earning Ratio) as a proxy of efficiency of investment as a function of Y (Firm Specific Stock Price Variation) as a proxy of firm specific information capitalization in stock price. We provide new evidence that Indonesian Capital Market does not efficient yet because the result at 2003 and 2004 does not consistent. With coefficient determination (IV) only 25.27% show that we should include another explanatory variable to explain about investment efficiencyKeywords: Firm-Specific Stock Price Variation, Investment Efficiency, Efficient Market Hypothesis